2017
DOI: 10.5194/acp-17-2741-2017
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical properties of frozen particles inferred from Global Precipitation Measurement (GPM) Microwave Imager (GMI) polarimetric measurements

Abstract: Abstract. Scattering differences induced by frozen particle microphysical properties are investigated, using the vertically (V) and horizontally (H) polarized radiances from the Global Precipitation Measurement (GPM) Microwave Imager (GMI) 89 and 166 GHz channels. It is the first study on frozen particle microphysical properties on a global scale that uses the dual-frequency microwave polarimetric signals.From the ice cloud scenes identified by the 183.3 ± 3 GHz channel brightness temperature (T b ), we find t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 41 publications
11
62
0
Order By: Relevance
“…Previous studies on the GMI snowfall detection capability assessment [18,26,33,43] demonstrate that GMI has great potential for snowfall observation. In this work, we have shown that, through the exploitation of all 13 GMI channels and the optimal use of ancillary variables describing the atmospheric conditions (and no ancillary information on the background surface conditions), SLALOM is able to predict snowfall occurrence and SWP, with a very good agreement with the Cloudsat 2CSP product, and has the advantage of ensuring a much larger spatial coverage, corresponding to the GMI swath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the GMI snowfall detection capability assessment [18,26,33,43] demonstrate that GMI has great potential for snowfall observation. In this work, we have shown that, through the exploitation of all 13 GMI channels and the optimal use of ancillary variables describing the atmospheric conditions (and no ancillary information on the background surface conditions), SLALOM is able to predict snowfall occurrence and SWP, with a very good agreement with the Cloudsat 2CSP product, and has the advantage of ensuring a much larger spatial coverage, corresponding to the GMI swath.…”
Section: Discussionmentioning
confidence: 99%
“…These sensors have high frequency channels that are highly sensitive to snowfall due to the scattering by snowflakes of upwelling terrestrial and radiation, originating in the lower levels of the atmosphere [15][16][17][18]. In addition, passive microwave radiometers have a large swath and have been installed on many platforms over the last decades, ensuring a good global coverage with a fair spatial resolution and lengthy data records.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies of PD from passive and active spaceborne measurements at visible and microwave wavelengths show that nonspherical ice crystals are not randomly oriented but usually horizontally oriented (Davis et al, , ; Defer et al, ; Prigent et al, , ; Zhou et al, ). Gong and Wu () (GW17 hereafter) first identified the similar features from the GPM‐GMI 166 and 89 GHz observations. Taking advantage of GPM's precession orbit, this paper aims to better understand the diurnal variation of PDs in the tropics and its implication for ice crystal's microphysical properties and how they vary together with macroscopic quantities such as cloud occurring frequency and mass.…”
Section: Introductionmentioning
confidence: 99%
“…Only the use of spheres for both snow and graupel leads to simulated brightness temperatures at 91.7 GHz which are colder than that at 183 GHz in the area of the hurricane precipitation (Figure b versus Figure b). Also, all of the CRTM simulations at 91.7 GHz (Figure ) have a cold bias to observations, even as the use of randomly oriented cloud and precipitation particles should be a source of positive bias to observations in 91.7 GHz simulations at horizontal polarization (e.g., Defer et al, ; Gong & Wu, ).…”
Section: Resultsmentioning
confidence: 99%